2022
DOI: 10.1016/j.jcis.2021.08.072
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms for hydroxyl radical production and arsenic removal in sulfur-vacancy greigite (Fe3S4)

Abstract: Herein, we systematically investigated the mechanisms of Å OH production and arsenic (As(III)) oxidation induced by sulfur vacancy greigite (Fe 3 S 4 ) under anoxic and oxic conditions. Reactive oxygen species analyses revealed that sulfur vacancy-rich Fe 3 S 4 (SV-rich Fe 3 S 4 ) activated molecular oxygen to produce hydrogen peroxide (H 2 O 2 ) via a two-electron reduction pathway under oxic conditions. Subsequently, H 2 O 2 was decomposed to Å OH via the Fenton reaction. Additionally, H 2 O was directly oxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…As some studies reported the concentration of sulfur vacancies in Fe 3 S 4 can be adjusted by altering the ratio of ethylene glycol to water during the synthesis process. 80,162…”
Section: Design Of Defectsmentioning
confidence: 99%
“…As some studies reported the concentration of sulfur vacancies in Fe 3 S 4 can be adjusted by altering the ratio of ethylene glycol to water during the synthesis process. 80,162…”
Section: Design Of Defectsmentioning
confidence: 99%
“…Furthermore, it has been found that by controlling the size of particles and reducing the sizes below 10 nm, the resultant TiO 2 quantum dots (TiO 2 QDs) presented outstanding photocatalytic performance due to improving textural properties, efficacious charge segregation, and changing redox potentials. , Greigite (Fe 3 S 4 ) is an iron–sulfur spinel with a crystalline structure, which is widely used in carbon dioxide reduction, nitrogen fixation, and environmental purification by removing heavy metals due to its ferromagnetic, environmentally friendly, cost-effective, and reducing properties. Furthermore, due to having a small energy gap, it can be simply excited by the sunlight illumination. , Greigite has abundant active sites due to the higher relative content of S 2– , Fe 3+ , and Fe 2+ on the surface, which leads to boosted photocatalytic performance …”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, due to having a small energy gap, it can be simply excited by the sunlight illumination. 17,18 Greigite has abundant active sites due to the higher relative content of S 2− , Fe 3+ , and Fe 2+ on the surface, which leads to boosted photocatalytic performance. 19 In this paper, we prepared S-scheme TiO 2 QDs/Fe 3 S 4 nanocomposites via a facile hydrothermal route.…”
Section: Introductionmentioning
confidence: 99%
“…Being the naturally abundant ferromagnetic iron-sulfur mineral, greigite (Fe 3 S 4 ) has been widely applied in heterogeneous AOPs. Liu et al [34,35] found an extensive peroxidase-like activity of Fe 3 S 4 , and applied Fe 3 S 4 to remove arsenic. Moreover, Shi et al [36] reported Fe 3 S 4 /H 2 O 2 system to degrade atrazine using •O 2 produced from O 2 under light irritation, demonstrating Fe 3 S 4 ′ s potential to activate O 2 for degrading organic pollutants.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Shi et al [36] reported Fe 3 S 4 /H 2 O 2 system to degrade atrazine using •O 2 produced from O 2 under light irritation, demonstrating Fe 3 S 4 ′ s potential to activate O 2 for degrading organic pollutants. On the other hand, the poor adsorption of dissolved O 2 onto the surface of the catalysts remains a major challenge for using O 2 to degrade contaminants [35,37]. Montemore et al [38] proposed a periodic trend in the of metal surfaces to O 2 activation that metals with a mostly empty d shell, such as Co, Fe, and Rh, presented extremely low adsorption and dissociation barriers.…”
Section: Introductionmentioning
confidence: 99%